2019
DOI: 10.1021/acs.jpca.9b05120
|View full text |Cite
|
Sign up to set email alerts
|

BrHgO + C2H4 and BrHgO + HCHO in Atmospheric Oxidation of Mercury: Determining Rate Constants of Reactions with Prereactive Complexes and Bifurcation

Abstract: Models suggest BrHgONO to be the major Hg­(II) species formed in the global oxidation of Hg(0), and BrHgONO undergoes rapid photolysis to produce the thermally stable radical BrHgO•. We previously used quantum chemistry to demonstrate that BrHgO• can, like •OH radicals, readily abstract hydrogen atoms from sp3-hybridized carbon atoms as well as add to NO and NO2. In the present work, we reveal that BrHgO• can also add to C2H4 to form BrHgOCH2CH2 •, although this addition appears to proceed with a lower rate co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…BrHg • produced in the reaction BrHgO • + CO → BrHg • + CO 2 can dissociate in competition with bimolecular reactions to make Hg­(II) compounds. , The larger the fraction of BrHgO • reacting with CO, the longer the residence time of mercury in the atmosphere and the greater the extent of mercury deposition as Hg(0) rather than Hg­(II) compounds. Previous work by Lam et al mapped out most competing types of reactions of BrHgO • . , Scheme depicts their results together with the findings of this work. BrHgO • is very effective at abstracting hydrogen atoms from sp-hybridized carbon atoms, and this reaction dominated the fate of BrHgO • in the analysis of Lam et al The model reaction was computed to proceed with a pseudo-first-order rate constant (at [CH 4 ] = 1.85 ppmv) of 11 s –1 at 298 K and 1 atm.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…BrHg • produced in the reaction BrHgO • + CO → BrHg • + CO 2 can dissociate in competition with bimolecular reactions to make Hg­(II) compounds. , The larger the fraction of BrHgO • reacting with CO, the longer the residence time of mercury in the atmosphere and the greater the extent of mercury deposition as Hg(0) rather than Hg­(II) compounds. Previous work by Lam et al mapped out most competing types of reactions of BrHgO • . , Scheme depicts their results together with the findings of this work. BrHgO • is very effective at abstracting hydrogen atoms from sp-hybridized carbon atoms, and this reaction dominated the fate of BrHgO • in the analysis of Lam et al The model reaction was computed to proceed with a pseudo-first-order rate constant (at [CH 4 ] = 1.85 ppmv) of 11 s –1 at 298 K and 1 atm.…”
Section: Resultsmentioning
confidence: 56%
“…Previous work by Lam et al mapped out most competing types of reactions of BrHgO • . 22,24 Scheme 1 depicts their results together with the findings of this work. BrHgO • is very effective at abstracting hydrogen atoms from sp 3 hybridized carbon atoms, and this reaction dominated the fate of BrHgO • in the analysis of Lam et al The model reaction…”
Section: Comparison To Oh + Comentioning
confidence: 90%
See 1 more Smart Citation
“…Only for syn ‐HgBrONO, recent computational work indicated that dissociation might occur rapidly in the lower atmosphere giving rise to HgBrO. This radical would further react with atmospheric trace gases, such as NO, NO 2 , and volatile organic compounds, to finally yield HgBrOH . However, in order to obtain a comprehensive and quantitative description of the atmospheric Hg chemical mechanism, the spectral properties and photodissociation reaction products of syn ‐HgBrONO, HgBrOOH, HgBrO, and HgBrOH need to be known, which are currently unexplored.…”
Section: Introductionmentioning
confidence: 68%
“…We now know that the oxidation of GEM is initiated by free radicals, most likely by atomic bromine, as shown in experimental, , theoretical, and modeling , studies. The resulting HgBr radical is relatively short-lived and must be stabilized via reactions with atmospheric species that are sufficiently reactive yet abundant, such as NO 2 and HO 2 , forming gaseous oxidized mercury (GOM) molecules like BrHgONO and BrHgOOH. , Recently, the first experimental study of the HgBr + NO 2 reaction kinetics has been reported, and future experiments must focus on identifying reaction intermediates and products . Meanwhile, the major focus of field studies has been to improve the limit of detection, accuracy, and temporal resolution of methods for the quantification of different forms of mercury in the atmosphere .…”
Section: Introductionmentioning
confidence: 99%